A Critical Examination of the Technological Pedagogical Content Knowledge Framework: Secondary School Mathematics Teachers Integrating Technology. (July 2015) - Stoilescu, Dorian
This study explores the Technological Pedagogical Content Knowledge (TPACK) for three experienced mathematics secondary teachers from a Toronto public school. By using a multiple case study, teachers' attitudes, skills, and approaches toward the use of Information and Communications Technology (ICT) in classrooms are described. By being aware of the three main facets of TPACK (technological, pedagogical, and mathematical aspects), the relative importance of each component and their intersections were scrutinized. Although from the same school, the teachers had very different conducts of showing their integration of ICT in mathematical pedagogy and therefore, their TPACK was different. Teachers demonstrated various strategies and different paces of adopting ICT: One teacher was a later adapter of ICT with strong emphasis in pedagogy, a second teacher was an early adapter of ICT with focus on finding an adequate technical support for mathematical content, and the third teacher was a very early adopter of ICT with extraordinary capabilities to reflect on the mathematics curriculum and continuingly adapt to his classrooms' needs. It was noticed that the teachers integrated technology to (a) help them describe the concepts to students; (b) motivate students to learn mathematics; (c) give students opportunities to experiment with mathematical concepts and skills; (d) assess, evaluate, and provide feedback to student's work, and (e) help them communicate mathematical solutions. Overall, the framework shows consistency in tracing their assorted routines of integrating technology in various classroom contexts. In the end, some considerations and insights on the potential of the TPACK framework are provided.